2018
DOI: 10.1063/1.5017303
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy distributions in highly transient EUV induced plasma in hydrogen

Abstract: This work reports on the measurements of ion flux composition and ion energy distribution functions (IEDFs) at surfaces in contact with hydrogen plasmas induced by extreme ultraviolet (EUV) radiation. This special type of plasma is gaining interest from industries because of its appearance in extreme ultraviolet lithography tools, where it affects exposed surfaces. The studied plasma is induced in 5 Pa hydrogen gas by irradiating the gas with short (30 ns) pulses of EUV radiation (k ¼ 10-20 nm). Due to the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 40 publications
(66 reference statements)
2
31
0
Order By: Relevance
“…Experimentally, no etching was measured at a grounded sample in 3 Pa H 2 while using a photon fluence of 5 × 10 19 cm −2 [64]. This agrees with the experimental ion energy distributions that were measured in [59] (<8 eV) and the threshold of 10 eV. By increasing the bias voltage, and thereby the ion impact energy, yields between 0.1 C/ion and 1 C/ion were found.…”
Section: Carbon Removalsupporting
confidence: 85%
See 3 more Smart Citations
“…Experimentally, no etching was measured at a grounded sample in 3 Pa H 2 while using a photon fluence of 5 × 10 19 cm −2 [64]. This agrees with the experimental ion energy distributions that were measured in [59] (<8 eV) and the threshold of 10 eV. By increasing the bias voltage, and thereby the ion impact energy, yields between 0.1 C/ion and 1 C/ion were found.…”
Section: Carbon Removalsupporting
confidence: 85%
“…to form H 3 + ions. Whereas, H 3 + has been recognized as the dominant ion in radiation-induced plasmas in H 2 background gas in outer-space, recent research has shown that this ion is also dominant under lithography scanner conditions on time scales longer than a few 100 ns after irradiation [59].…”
Section: Dynamics Of Euv-induced Plasmasmentioning
confidence: 99%
See 2 more Smart Citations
“…High temperature, dense plasmas in fusion reactors [1], diffuse plasmas induced by extreme ultraviolet radiation [2] and dense low pressure plasmas in laboratory ion sources and for electric propulsion [3]. Plasma facing materials (PFMs), such as divertors in fusion reactors are bombarded by hydrogen and deuterium ion species [4], ion lensing systems for electric propulsion technology deteriorate under xenon ion impingement and optics in next generation lithography applications face diffuse hydrogen and nitrogen plasmas [5,6].…”
Section: Introductionmentioning
confidence: 99%